PERSPEKTIF “FAMILY SYSTEM INTERVENCY” UNTUK PROTEKSI KARAKTER KEBAJIKAN SISWA SMA - Hambali, IM (Jurnal Kajian Bimbingan dan Konseling, 2016)
Today's high school students receive sharp attention from society. This happened because there were many bad incidents involving high school students, including brawls between high school students. The family system perspective study is an argument that provides insight into how family involvement in formal education can be implemented. This research uses a qualitative approach with the type of library research. This research aims to explain how a family intervention perspective can contribute to the implementation of independent character education. The results of this study show that although the idea of family intervention is developing in North American families, Indonesian culture has not developed well. Meanwhile, this family intervention perspective can be considered as a comprehensive perspective of school counselors and can be a bridge for solving student problems. In accordance with the basic idea, which explains that individuals live, develop and change cannot be separated from the structure and influence of the family, students as an important part of family life are subjects who participate in forming an overall family structure. In this article there is a description of the intervention perspective and the possibility of its application in the context of comprehensive character education.